El auge de la derecha en la crisis posneoliberal en América Latina: casos Brasil y Argentina - Tipismana Arriola, José Arturo (2019)
This paper focuses on two case studies, Brazil and Argentina, in which, after several years of leftist governments, two right-wing candidates succeeded and became president. These are Jair Bolsonaro, who was a candidate of the Social Liberal Party and is the current president of Brazil; and Mauricio Macri, who won the presidency of Argentina with the right-wing Coalition Cambiemos. Considering the results of the last presidential elections, it seems that in Argentina this right turn could not be sustained over time; meanwhile, in Brazil, the Partido de los Trabajadores achieve a relevant presence in Parliament. This paper concludes that this turn to the right did not happen because it was not a political turn like the pink tide. Three explanatory factors are considered: economic performance, the credibility of leftist leaders and the strength of the right. From there, each case will be thoroughly analyzed, and then compared. The result of this process is the finding of substantial differences, especially regards the economic crisis and the strength of the right. Finally, the reflections regarding the findings sustain that these electoral results only represent the attrition of leftist governments due to the great corruption scandals and the curb economic growth, and not necessarily the beginning of a new era in Latin American politics.